A New Dimension for Coordination Polymers and Metal–Organic Frameworks: Towards Functional Glasses and Liquids. Issue 17 (20th February 2020) - Horike, Satoshi; Nagarkar, Sanjog S.; Ogawa, Tomohiro; Kitagawa, Susumu
Abstract: There are two categories of coordination polymers (CPs): inorganic CPs (i‐CPs) and organic ligand bridged CPs (o‐CPs). Based on the successful crystal engineering of CPs, we here propose noncrystalline states and functionalities as a new research direction for CPs. Control over the liquid or glassy states in materials is essential to obtain specific properties and functions. Several studies suggest the feasibility of obtaining liquid/glassy states in o‐CPs by design principles. The combination of metal ions and organic bridging ligands, together with the liquid/glass phase transformation, offer the possibility to transform o‐CPs into ionic liquids and other ionic soft materials. Synchrotron measurements and computational approaches contribute to elucidating the structures and dynamics of the liquid/glassy states of o‐CPs. This offers the opportunity to tune the porosity, conductivity, transparency, and other material properties. The unique energy landscape of liquid/glass o‐CPs offers opportunities for properties and functions that are complementary to those of the crystalline state. Abstract : Heart of glass : The liquid/glass states of coordination polymers (CPs) and metal‐organic frameworks (MOFs) constitute a new class of amorphous materials and are related to ionic liquids and other ionic soft materials. The unique energy landscape and dynamics of liquid/glass CPs/MOFs with coordination networks offer additional opportunities for properties and functions that are complementary to those of the crystalline state.